Shock Pulse Shaping in a Small-Form Factor Velocity Amplifier. (2010) - Kelly, Gerard; Punch, Jeff; Goyal, Suresh; Sheehy, Michael
Abstract : This theme of this paper is the design and characterisation of a velocity amplifier (VAMP) machine for high-acceleration shock testing of micro-scale devices. The VAMP applies multiple sequential impacts to amplify velocity through a system of three progressively smaller masses constrained to move in the vertical axis. Repeatable, controlled, mechanical shock pulses are created through the metal-on-metal impact between pulse shaping test rods, which form part of the penultimate and ultimate masses. The objectives are to investigate the controllable parameters that affect the shock pulses induced on collision, namely; striker and incident test rod material; test rod length; pulse shaping mechanisms; and impact velocity. The optimum VAMP configuration was established as a 60 mm long titanium striker test rod and a 120 mm long titanium incident rod. This configuration exhibited an acceleration magnitude and a primary pulse duration range of 5, 800–23, 400 g and 28.0–44.0 μ s respectively. It was illustrated that the acceleration spectral content can be manipulated through control of the test rod material and length. This is critical in the context of practical applications, where it is postulated that the acceleration signal can be controlled to effectively excite specific components in a multi-component assembly affixed to the VAMP incident test rod.